Hydrocarbon biomarkers in coals from Sungai Mas, Mukah-Balingan and Merit Pilla Sarawak - Azulyana, Aziz. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Coal samples Merit pilla, Sungai Mas and Mukah-Balingian were studied qualitatively and quantitatively to determine the distribution of hydrocarbon. The coal samples were extracted with Soxhlett extraction method and fractionated on silica gel column chromatography to get the aliphatic (Fl) and aromatic (F2) fraction. The aliphatic and aromatic fraction were analysed using gas chromatography/flame ionization detector (GC/FID) and gas chromatography/mass spectrometry (GC/MS). Proximate analysis showed that the organic matter and volatile for the Merit Pilla and Mukah-Balingian is more than 80% with a moisture content (11.77% for Merit Pilla and 24.64% for Mukah-Balingian) low volatile matter for Sungai Mas coal samples (45.57%) with a quite low of moisture content (2.79%). Biomarkers study based from the nalkanes distribution, ratio of isoprenoids groups, isoprenoid/n-alkanes and CPI values gives the information to support the origin of these coal samples either from the higher terrestrial plants with the higher content of wax or evolved from algae, bacteria and zooplankton. The quantitative analysis were done to the aromatic hydrocarbon fraction (F2) to determine the distribution of aromatic hydrocarbon in the coal samples. The aliphatic fraction (Fl) was further analysed by GC/MS to determine the quantitative distribution of n-alkanes, hopanes, diterpanes and triterpanes compound which are consistent to higher plants.